Application of cryogenic grinding for filler preparation in the form of Coconut Nanocomposites into the Thermoplastic Matrix with the evaluation of properties while using different types of MAgPP Coupling agents / Petr Lenfeld...[et al.] - Petr, Lenfeld; Luboš, Běhálek; Martin, Borůvka (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The application of natural plant materials as fillers in polymeric materials is currently a very interesting area of research in order to achieve specific properties of polymer composites with a potential of the particular application in various industrial fields. One of these areas is the research concerning cryogenic grinding application for the preparation of nanoparticles from natural materials and the use of such prepared fillers in polymer matrices of a synthetic or natural origin. This paper focuses on the implementation of nanoparticles produced by cryogenic grinding of natural coconut fibers into a polypropylene matrix, evaluating the effects of different types of MAgPP coupling agents providing sufficient wettability and therefore compatibility at the interface between the hydrophobic polymer matrix and natural fillers, on final properties of polymeric nanocomposites.